The financial crisis and the systemic failure of academic economics - David C. Colander; Hans Föllmer; Armin Haas; Michael Goldberg; Alan Kirman; Katarina Jusélius; Thomas Lux; Brigitte Sloth (Kiel Institute for the World Economy (IfW), 2009)
The economics profession appears to have been unaware of the long build-up to the current worldwide financial crisis and to have significantly underestimated its dimensions once it started to unfold. In our view, this lack of understanding is due to a misallocation of research efforts in economics. We trace the deeper roots of this failure to the profession's insistence on constructing models that, by design, disregard the key elements driving outcomes in real-world markets. The economics profession has failed in communicating the limitations, weaknesses, and even dangers of its preferred models to the public. This state of affairs makes clear the need for a major reorientation of focus in the research economists undertake, as well as for the establishment of an ethical code that would ask economists to understand and communicate the limitations and potential misuses of their models.
Keywords: A11; B40; G01; 330; Financial crisis; academic moral hazard; ethic responsibility of researchers; Wirtschaftswissenschaftler; Verantwortung; Moral Hazard; Wirtschaftstheorie; Wirtschaftsmodell; Finanzmarktkrise; Kritik